Software systems safety - Grumberg, Orna; Seidl, Helmut (Computer scientist); Irlbeck, Maximilian (NATO science for peace and security series. Information and communication security, 2014)
Until quite recently, the correctness and security of software systems was a largely theoretical problem relevant only for a small group of computer specialists. Today it is a fundamental problem for society at large, with security breaches in banking software, malware attacks and bugs in programs affecting millions of people and making the headlines almost daily. The computer science community is developing verification and synthesis tools which will mechanize ever more tasks in the design of secure programs. This book presents the papers delivered at the NATO Advanced Study Institute (ASI) S.